DETERMINANTS OF TECHNICAL EFFICIENCY AND TOTAL FACTOR PRODUCTIVITY CHANGE OF THE MANUFACTURING INDUSTRY IN EAST JAVA: EFFORTS TO INCREASE PERFORMANCE AND INDUSTRIAL COMPETITIVENESS - Imroatul Amaliyah (East Java Economic Journal, 2018)
This research aims to calculate and analyze the level of technical efficiency and total factor productivity change of manufacture industry, and to examine the factors that influence the value of technical efficiency of manufacture industry in East Java. The method used for this research is Data Envelopment Analysis (DEA) and Malmquist Index with Bootstrapping approach, and Tobit regression. This research used micro data from Indonesian Large and Medium-Scale Industry Survey within the year of 2007 to 2013. The results of this research are: (1) the estimated result of DEA with bootstrapping approach using output-oriented variable return to scale (VRS) assumption shows that the level of technical efficiency of manufacture industry in East Java has been not good enough and overall, it still has the potential to increase its output to reach an efficient condition; (2) the estimated result of Tobitregression demonstrates that the level of technical efficiency of the company is influenced by the company’s size, HHI, capital labor ratio, export and types of company ownership; (3) the estimated result of Malmquist Index with Bootstrapping approach shows that theaverage of total factor productivity change (TFPCH) of manufacture industry from 2007 to 2013 hasexhibited a positive change. The main factor that affects TFPCH, in order, are technological change, efficiency change, and efficiency scale change.